Water Vapor Flux‐Profile Relationship in the Stable Boundary Layer Over the Sea Surface. Issue 16 (25th August 2022) - Ma, Yubin; Cheng, Xueling; Li, Qilong; Wu, Lin; Zeng, Qingcun; Jin, Jiangbo; Shao, Shiyong; Li, Junmin; Han, Chenghui
Abstract: Comprehensive marine atmospheric turbulence observation data, meteorological sounding and sea surface conditions in the South China Sea were employed to analyze and parameterize the vapor profile in the stable marine atmospheric boundary layer. The observations involved a three‐dimensional ultrasonic anemometer, water vapor carbon dioxide analyzer, radiosonde, and buoy. This paper theoretically determined that the water vapor profile function φ q differs from the temperature profile function φ h and that φ q should be independently parameterized. A linear relationship existed between the dimensionless water vapor gradient and stability parameters based on the observation results, and φ q was then obtained as φ q ( z / L ) =  az / L  +  b, in which the stability covered the stability range ( z / L  > 1). This result was applied in the Tropical Ocean‐Global Atmosphere Coupled‐Ocean Atmosphere Response Experiment bulk flux algorithm, and the simulation of the latent heat flux was improved. Plain Language Summary: Monin and Obukhov established the relationship between momentum flux and temperature flux and their respective vertical gradients. Using these two relations and some parameterization methods, we can calculate momentum flux and sensible heat flux. However, there is no physical basis for the above relationship for latent heat flux, and the effect of vertical distribution of water vapor on latent heat flux is not taken into account. In this paper, the relationship between water vapor flux and water vapor gradient is established and verified by marine observation data. Thus it can have more physical meaning and calculate the latent heat flux more accurately. This study is useful for understanding the boundary layer and model development. Key Points: The linear relationship between the dimensionless specific humidity gradient and the stability parameter is established The temperature mixing length is longer than the specific humidity, and water vapor is more difficult to transfer in the vertical direction The vertical distribution of water vapor has an important influence on the parameterization of water vapor flux